Preface of the 3rd International Electronic Conference on Processes (ECP 2024) - Giancarlo Cravotto (Engineering Proceedings, 2024)
The 3rd International Electronic Conference on Processes—Green and Sustainable Process Engineering and Process Systems Engineering (ECP 2024) was hosted online from 29 to 31 May 2024 [...]